Defining the multifaceted roles of dental academics: A consensus approach using the Fuzzy Delphi Method - Norasmatul Akma Ahmad; Noor Hayaty Abu Kasim; Sabri Musa; Siti Adibah Othman; Zahra Naimie (PLoS ONE, 2025)
Dental academics are the foundation of dental institutions. They are mostly dental specialists and scientists driven by a passion for teaching and intellectual challenges. Although most have not been trained or certified as educators, they are tasked with educating the next generation of dentists within their fields of expertise. Beyond teaching, dental academics juggle multifaceted roles as educators, researchers, administrators, and clinicians. The effort to balance these multiple roles may lead dental academics to face identity conflicts, loss of work satisfaction and ultimately burnout and attrition from the workforce. Given the limited literature on defining faculty competencies and roles in medical and dental education, and an ongoing retention issues, it is crucial to clearly delineate these roles to assist dental academics establish their academic identity and plan their careers. This study aims to systematically define the specific roles of dental academics using the Fuzzy Delphi Method (FDM). Engaging 27 experts in the first round and 23 in the second, consensus was reached on items derived from evidence-based literature to define these roles. Analysis yielded 17 accepted items representing the four main roles of dental academics. Each primary role encompassed a diverse range of job descriptions, precluding a single, definitive description. The application of FDM not only refines the understanding of academic roles but also contributes to establishing the identity of dental academics, aiding their adaptation to the multiple roles and supporting their career advancement.